Sequence anatomy of mitochondrial anion carriers - Jezek, Petr; Jezek, Jan (FEBS letters, 2003)
Two hundred and eighty-four genes of eight eukaryotic genomes for mitochondrial anion carriers were sorted into 43 (+18 single protein) subfamilies. Subfamilies differ by the number, nature, and locations of charges and polar residues in the transmembrane alpha-helices. Consequently, these residues and the rarely unique residues of the matrix and cytosolic segments most likely determine the different molecular phenotypes (functions). 'Common ancestral hydrophilic segments' were found in matrix and cytosolic segments, with interchangeable polar residues. Thus the hydrophobic microstructures of hydrophilic carrier parts are supposed to predetermine structure/conformation, whereas polar and charged microstructures should predetermine function, namely in the transmembrane spanning alpha-helices.
Keywords: Animals; Sequence Analysis, Protein; Protein Structure, Tertiary; Mitochondria; sekvence aminokyselin; terciární struktura proteinů; lidé; Amino Acid Sequence; proteiny přenášející anionty; mitochondrie; Anion Transport Proteins; Protein Conformation; konzervovaná sekvence; konformace proteinů; cytosol; Cytosol; zvířata; sekvenční analýza proteinů; Conserved Sequence; Humans